Analisis Teori Konstruktivisme Sosial Vygotsky dalam Pembelajaran Kolaboratif Berbasis Teknologi Digital - Rizal Bakti; Amin Saleh‎; Arwin Tannuary (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Vygotsky's social constructivism offers a relevant epistemological framework for understanding how knowledge is constructed collaboratively through social interaction mediated by cultural tools, including digital technology. This study aims to analyze the key concepts of Vygotsky's theory, particularly the Zone of Proximal Development (ZPD), scaffolding, and the More Knowledgeable Other (MKO), and to examine their relevance to technology-supported collaborative learning in twenty-first-century education. This research employed a Systematic Literature Review by examining peer-reviewed articles, academic books, and research reports published mainly between 2018 and 2024, with classic theoretical works used as foundational references. Literature was searched through Google Scholar, ERIC, JSTOR, and Scopus using defined keywords and inclusion-exclusion criteria. The findings show that Vygotskyan principles can be operationalized through Learning Management Systems, collaborative document platforms, video conferencing tools, online forums, and AI-assisted learning systems. These platforms function as digital mediating tools that extend learners' ZPD and support teacher-student as well as peer-to-peer scaffolding. Strategies such as digital peer tutoring, online think-pair-share, collaborative document editing, flipped classroom, and project-based digital collaboration provide practical models for strengthening interaction, shared meaning-making, and learner autonomy. The novelty of this study lies in synthesizing Vygotsky's social constructivist concepts into a digital collaborative learning framework that is contextually relevant for Indonesian education. The study implies that digital learning design should not merely focus on technology adoption, but should integrate pedagogical scaffolding, teacher digital competence, and equitable access to learning infrastructure.